Pengaruh Anggaran Pendidikan dan Anggaran Kesehatan Terhadap Indeks Pembangunan Manusia Kota Kendari - Rizal Rizal (Kayee: Jurnal Pendidikan dan Ilmu Sosial, 2026)
This study aims to analyze the influence of education and health budgets on the Human Development Index (HDI) in Kendari City during the period 2019-2025. The research employs a quantitative method with a time series approach and multiple linear regression analysis. The results indicate that both education and health budgets consistently increased over the period, accompanied by an improvement in HDI despite a decline in 2020 due to the COVID-19 pandemic. Statistical tests reveal that both budget variables have a positive and significant effect on HDI, both partially and simultaneously, with a contribution of 85.6%. These findings reinforce human capital theory, which states that investment in education and health enhances the quality of human resources and overall human development. The study underscores the importance of effective budget management and the commitment of local governments to improve community welfare through the education and health sectors in Kendari City